2020
DOI: 10.3390/app10051609
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Daily Temperatures with Different Time Interval Data Using Deep Neural Networks

Abstract: Temperature forecasting has been a consistent research topic owing to its significant effect on daily lives and various industries. However, it is an ever-challenging task because temperature is affected by various climate factors. Research on temperature forecasting has taken one of two directions: time-series analysis and machine learning algorithms. Recently, a large amount of high-frequent climate data have been well-stored and become available. In this study, we apply three types of neural networks, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…This method has two convolutional layers, and each layer is followed by a batch normalization layer, ReLu layer, MP Layer of stride 2, and dropout layer with a dropout probability of 0.2. The performance consists of as many values as the number of filters and is connected to the FCL to predict APT [20].…”
Section: A Convolutional Neural Network (Cnn) Modelmentioning
confidence: 99%
“…This method has two convolutional layers, and each layer is followed by a batch normalization layer, ReLu layer, MP Layer of stride 2, and dropout layer with a dropout probability of 0.2. The performance consists of as many values as the number of filters and is connected to the FCL to predict APT [20].…”
Section: A Convolutional Neural Network (Cnn) Modelmentioning
confidence: 99%
“…ANNs, including Multilayer Perceptron, deep ANNs, and other machine learning models, are constantly being improved and widely used for the forecasting of air temperature [64], rainfall [36,37,65], cloudiness [66], and wind speed [67], which proves that these are forward-looking models that are worthy of constant research and improvement for forecasting purposes. To summarize, the most frequently forecasted condition in the above works was temperature; several studies have similarly found the use of models for wind speed prediction, and the most frequently used machine learning model for this purpose was a multilayer Artificial Neural Network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CNNs are particularly useful for finding patterns in images to recognize objects, faces, and scenes. They can also be quite effective for classifying non-image data such as audio, time series, and signal data [64][65][66][67][68][69][70][71][72][73]. Figure 9 shows an example of image classification using a CNN [65].…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%